Regioselective hydrothiolation of allenoates through a Ca(OTf)2-promoted three-component reaction - Abdi, Aida; Hosseini, S. Sina; Nikbakht, Ali; Bijanzadeh, Hamid Reza; Rominger, Frank; Balalaie, Saeed (ChemistrySelect, 2022)
An approach to synthesize α-substituted alkene derivatives via calcium-promoted hydrothiolation of allenoates is described. Employing diverse allenoates, and amines, a library of α-substituted alkenes is obtained with great regioselectivity and good to high yields. The reaction proceeds through the nucleophilic addition of in-situ generated dithiocarbamates to allenoates in a rapid mild method using an eco-friendly metal promoter.